Mediadores da fé: análise do ethos de pregadores carismáticos - Eleutério, Daniele Giacomo (2016)
In order to characterize the genre "religious preaching", through previous research undertaken by Figueiredo et al. (2009), it was possible to understand some peculiarities present in these oral texts produced by religious leaders. It was then that we saw that it is a strictly oral genre, produced by a religious leader and has, as recipients, faithful belonging to a common group. With a minimum duration of time, often previously established, religious preaching is produced in communities that have written references and use these parameters in its composition. To deepen this theme in this work, we will seek to describe the speaker's ethos performance in religious preaching, in order to reflect on its persuasive scope and its implications for the rhetorical-argumentative constitution of that genre. Still within this purpose, we present the concepts of ethe of phronesis, arete and eunoia to investigate their incidence in these speeches. For this, we will use authors from the rhetorical field who had contributed to the reflection of the role played by the speaker and its implications for the persuasive process. Therefore, we will count with the contributions of Aristotle, Perelman and Olbrechts-Tyteca, Meyer, Reboul, Eggs, Fiorin, among others. For the choice of the corpus, we consider the fact that in the last three decades, the Catholic Church, especially in Brazil, has sought to propagate a new form of evangelization led by the Charismatic Renewal. Due to the significant number of followers and the contemporary style of preaching, the priests Father Fabio de Melo, Monsignor Jonas Abib and Father Leo were elected as representatives of the media Catholicism of the 21st century. Among their vast productions – CDs, DVDs, books, sermons and television programs – we have selected, as the corpus of this research, a preaching from each of the elected priests. The three elected sermons are available on CD and DVD. Through the corpus analysis, we understand the presence of rhetorical-argumentative elements that served as the guiding principle of the speeches delivered by the priests, who, through their preaching, sought to ensure greater adherence of the faithful. Aware of the persuasive power of religious discourse delivered by the selected priests, the analysis undertaken by us aimed to contribute to the understanding of the rhetorical implications of the preacher ethos within the analyzed genre: the "religious preaching." The analysis results allowed us to verify the recurrence of ethe phronesis, arete and eunoia in each preaching that constituted the corpus. Thus, we concluded that, although we are dealing with same genre, the manifested ethe in each of the preachings did not show stability, but rather varied according to each speaker.